DAMPAK USAHA PENGOLAHAN IKAN PT. ARTA MINA JAYA TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT DI DESA ANTAPIA KECAMATAN WANGI-WANGI KABUPATEN WAKATOBI - Novita Zulhera Jaenudin; Muhammad Rafiy; Nur Azisah (JEP (Jurnal Ekonomi Pembangunan), 2019)
Research objectives: To determine the impact of the socio-economic conditions of the community in Antapia Village, Wangi-Wangi District, Wakatobi Regency, the determination of the sample uses the Slovin formula. The number of samples was 52 people. The analytical method used is descriptive quantitative describing the socioeconomic conditions of the community as a result of the Fish Processing business of PT. Arta Mina Jaya in the Village of Antapia.The results: (1) fish Processing has a positive impact on community economic activities. Before the existence of Fish Processing most people work as farmers and fishermen but after the Fish Processing economic activity increases. The community gets additional work as food and beverage traders, ice cube sellers and the opening of new stalls around  (2) Fish Processing also has an impact on people's income, which before level of income of respondents is still relatively low as many as 19 respondents (36.53%) have an average income of between Rp. 650,000 to 870,000 per month. After the existence of increased the income of respondents to 27 respondents (51.92%) and respondents whose average income between Rp. 1,251,000 to Rp. 3,250,000 per months increased to 25 respondents (48.08%).